PENGARUH KEPUASAN GAJI TERHADAP TURNOVER INTENTION DENGAN KOMITMEN ORGANISASIONAL SEBAGAI MEDIASI PADA RUMAH SAKIT UMUM PREMAGANA - Putra, Ida Bagus Ketut Surya, Dede Kresna (E-Jurnal Manajemen; Vol 5 No 7 (2016), 2016)
The purpose of this study was to analyze the effect of pay satisfaction on turnover intention, to analyze the influence of organizational commitment to turnover intention, to analyze the influence of satisfaction on salary to turnover intention and analyze the influence of organizational commitment as mediating the relationship between satisfaction over salary with turnover intention of employees RSU Premagana. This research was conducted at the General Hospital-Premagana Batubulan Gianyar. The samples used were 107 employees. Data were collected by interviews, surveys and questionnaires. Data analysis technique used is path analysis. These results indicate that salary satisfaction and significant negative effect on turnover intention. Organizational commitment and significant negative effect on turnover intention and pay satisfaction and significant negative effect on turnover intention through the mediation of organizational commitment at General Hospital-Premagana Batubulan Gianyar. Keywords: Salary Satisfaction, Organizational Commitment, Turnover Intention
Keywords: Salary Satisfaction, Organizational Commitment, Turnover Intention